Analisis Pengaruh Dimensi Caring terhadap Pengambilan Keputusan Perawat pada Proses Asuhan Keperawatan Berdasar Teori Swanson - Rachmaningsih, Nurul; Saudah, Noer; Azizah, Lilik Ma’rifatul (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the Caring dimension of nurses' decision-making in the nursing care process. The research method used a correlational analytical design with a cross-sectional approach with a sample of 116 nurses used a simple random sampling technique, data collection using The Caring Assessment for the Direct care Giver (CACG) questionnaire for the independent variable of the Caring dimension, and The Clinical Decision Making in Nursing Scale (CDMNS) questionnaire for the dependent variable of decision-making, the data was analyzed using logistic regression with a p ≤ value of 0.05. The results showed that the dimensions of maintaining belief (0.029), knowing (0.030), being with (0.009), doing for (0.031), and enabling (0.039) had a significant influence on decision-making in the nursing care process. Conclusion, the dimensions of Caring maintaining belief, knowing, being with, doing for, and enabling can have an influence on quality nursing services for patients. Keywords: Caring, Decision Making, Nursing Care